2022
DOI: 10.1128/spectrum.01324-22
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiome Dysbiosis in Women with Intrauterine Adhesions

Abstract: Intrauterine adhesion (IUA) often leads to hypomenorrhea, amenorrhea, repeat miscarriages, and infertility. It has been prevalent over the last few decades in up to 13% of women who experience pregnancy termination during the first trimester, and 30% of women undergo dilation and curettage after a late, spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Although it has been touched upon in the previous sections of this review, it is important to reiterate the significance of the mycobiome and how dysbiosis in any part of a microbiome can have severe consequences on host health, as well as other communities within the overall microbiome [ 51 ]. While the contributions of bacterial microbiome dysbiosis toward disease have been thoroughly studied, mycobiome dysbiosis has been heavily neglected [ 52 ]. Dysbiosis of the mycobiome occurs from various factors, but some common ones include diet, skin contamination, lifestyle activities, medical treatments or pharmaceuticals, environmental factors, and hygiene practices [ 53 ].…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been touched upon in the previous sections of this review, it is important to reiterate the significance of the mycobiome and how dysbiosis in any part of a microbiome can have severe consequences on host health, as well as other communities within the overall microbiome [ 51 ]. While the contributions of bacterial microbiome dysbiosis toward disease have been thoroughly studied, mycobiome dysbiosis has been heavily neglected [ 52 ]. Dysbiosis of the mycobiome occurs from various factors, but some common ones include diet, skin contamination, lifestyle activities, medical treatments or pharmaceuticals, environmental factors, and hygiene practices [ 53 ].…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
“…One area of mycobiome dysbiosis that has important implications for women is in the vaginal microbiota community [ 52 ]. In a study of intrauterine adhesion (IUA) disease, it was found that certain fungal genera, such as Filobasidium and Exophiala , are more enriched in IUA samples versus healthy subjects [ 52 ]. It has also been shown that fungal–bacterial patterns and interactions exist in this region.…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
“…The study of intrauterine adhesion patients described Candida -related differences in the gut mycobiome composition and numerous fungal–bacterial correlations in cervical canal and middle vagina sites [ 154 ]. There are multiple studies describing the role of Candida strains in the context of vaginal pathophysiology, but there are no studies describing the comprehensive impact of vaginal mycobiome dysbiosis on women´s health.…”
Section: Genitourinary Tract Mycobiomementioning
confidence: 99%
“…Reproductive tract fungal infections can have serious effects on women's professional and personal lives 8 , 9 . Harnessing 16S and ITS2 rDNA sequencing analysis, our previous study found that the fungal genera were enriched in the lower genital tract of IUA patients 10 . Moreover, site-specific fungal-bacterial correlation networks were discovered in those patients 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing 16S and ITS2 rDNA sequencing analysis, our previous study found that the fungal genera were enriched in the lower genital tract of IUA patients 10 . Moreover, site-specific fungal-bacterial correlation networks were discovered in those patients 10 . Vaginal candidiasis is the most common vaginal fungal infection 11 .…”
Section: Introductionmentioning
confidence: 99%